Sign System as Visual Communication for SMEs in Malang - Idris, Idris; Purnomo, Agus; Adi, Khofifatu Rohmah (International Journal of Community Service Learning, 2022)
Small and Medium Enterprises (SMEs) is one of the fields whose presence can help the regional or national economy. SMEs also have an influence on the absorption of labor. This paper aims to to develop a sign system as a visual communication in the Tasik Madu area. This service is carried out through several stages, Pre-Activity, Implementation of Activities and Post-Activities. Pre-activities are carried out by starting a survey of the location where the sign system will be installed, after finding the location for the installation of road signs, the next thing to do is to design a road sign design and place an order for a sign system. Then, there is the implementation of activities whose activities include the installation of a sign system at a predetermined location. This activity was carried out by students, lecturers as well as representatives of local environmental officials. The last stage is post-activity whose activities include closing and compiling community service reports. The development of the sign system is expected to be a visual communication so that it is easier for visitors to find the location of each woven craftsman in Tasik Madu.